"But Everyone Else is Doing It:" A Social Norms Perspective on Classroom Incivility. Issue 4 (2nd October 2018) - Segrist, Dan; Bartels, Lynn K.; Nordstrom, Cynthia R.
Abstract: Classroom incivility includes many student behaviors that detract from learning, such as texting, carrying on side conversations, leaving class early, etc. Uncivil behaviors distract faculty and students during class time and undermine the learning environment. This study examines classroom incivility from a social norms perspective. Social norms have been found to be powerful predictors of behavior in many contexts. In this study, we asked students to rate the frequency of classroom incivilities (descriptive norms) and the appropriateness of uncivil behaviors (injunctive norms) for themselves and for "most college students." We found that social norms were strong predictors of classroom incivilities. The more that students believed that most college students engaged in classroom incivilities, the more the students engaged in these uncivil behaviors themselves. These findings suggest classroom interventions targeting social norms may be effective in reducing classroom incivilities. Future research should examine the influence of other norm comparison groups.